Controversies in Oral Cancer - Pathak, K. Alok; Nason, Richard W. (Head and Neck Cancer Clinics, 2012)
This volume brings together the work of experts from clinical and basic sciences specialties and addresses some of the controversial issues and advances in the management of oral cancer. Improving the outcome for the oral cancer patient will require dedicated work from many disciplines working together as multidisciplinary units. The book is meant for medical students, residents and consultants in various disciplines, including otolaryngology, head and neck surgery, neurosurgery, plastic surgery, maxillofacial surgery and oncology.